Electropolymerized AIE‐active polymer film with high quantum efficiency and its application in OLED. Issue 4 (17th November 2016) - Li, Jinyu; Han, Xiao; Bai, Qing; Shan, Tong; Lu, Ping; Ma, Yuguang
ABSTRACT: A carbazole functionalized electro‐active AIE‐activity molecule, TPE‐DFCz, was designed, synthesized, and well characterized. The clear difference in oxidation potentials between tetraphenylethylene (TPE) unit and carbazole groups was found which guaranteed that polymerization occurred only at the peripheral carbazole groups and the TPE unit remained unchanged. Its luminescent network film was prepared conveniently by electrochemical polymerization (EP). The cross‐linked film exhibited green emission with high quantum efficiency of 63%, relatively smooth surface, and good thermal stability. The effect of different scan cycles on the optical property was also investigated. The electroluminescent device using the optimized polymer film as active layer showed a maximum luminance of 3200 cd m −2 and a maximum luminance efficiency of 1.16 cd A −1 with very low roll‐off of the efficiency. The AIE‐active EP films afford more opportunities to develop polymer films with high quantum efficiency via a simple, effective method and promote the potential applications in display devices. © 2016 Wiley Periodicals, Inc. J. Polym. Sci., Part A: Polym. Chem.2017, 55, 707–715 Abstract : A new AIE molecule, TPE‐DFCz, is obtained and its luminescent network film is prepared conveniently by electrochemical polymerization. The cross‐linked film exhibits high quantum efficiency of 63%, relatively smooth surface, and good thermal stability. OLEDs using the polymerized film as the active layer show a maximum luminance of 3200 cd m −2 and a maximum luminance efficiency of 1.16 cd A −1 with very low roll‐off of the efficiency.